Facial candling for the treatment of allergic rhinitis in young adults: A qualitative study - Nor Faizatul F Ismail; Chin Fen Neoh; Qi Ying Lean; Amir H Abdullah; Siong Meng Lim; Kalavathy Ramasamy; Rahul P Patel; Long Chiau Ming; Yee Chang Soh (Wolters Kluwer Medknow Publications, 2018)
Aims: Facial candling is one of the traditional treatments that is claimed to be able to help in curing or reducing various allergy and inflammation conditions such as allergic rhinitis. We aimed to explore the perceptions of participants with allergic rhinitis toward their disease conditions and facial candling treatment. Materials and Methods: The study used a qualitative exploratory design, comprising 12 in-depth interviews. A semi-structured topic guide was used to explore all relevant aspects of the topic, which were audio recorded, transcribed verbatim. All the interviews were conducted in a few beauty salons in purposively selected city areas in the state of Kedah, Malaysia. Results: Of the 12 patients, seven (58%) reported a positive experience of facial candling treatment, with improvement in the condition of their allergic rhinitis. Specific themes about the experience of facial candling treatment that were identified within the transcript data included knowledge about facial candling, options for disease treatment, effectiveness of facial candling, sources of information, comparison, application of treatment, treatment budget, and safety. The major strength lies in the fact that reasons for using facial candling were uncovered from the perspectives of people with allergic rhinitis through the in-depth interviews. Conclusions: The motives of these participants for using facial candling are mainly due to cultural influence and its low cost of treatment. There were mixed responses from the participants about the usefulness of facial candling. Most of the respondents had not assessed the safety of prolonged use of facial candling and regarded it as a safe procedure as this has been practiced for generations.